Perceptions of Online Motorcycle Taxi Drivers Regarding the Risk of Occupational Diseases and Work Accidents - Dewanti, Annisa Meutia (BKM Public Health and Community Medicine, 2024)
Purpose: This study aims to identify the barriers faced by online motorcycle taxi drivers, understand their perceptions of occupational diseases (PAK) and work accidents, and examine the rules and facilities provided by companies to support the implementation of occupational health and safety (K3) principles. Methods: This qualitative study uses a phenomenological approach. Informants were online motorcycle taxi drivers selected through purposive sampling based on inclusion and exclusion criteria. Data were collected through in-depth interviews supported by observations. The data analysis was inductive. Results: The informants were male, aged between 30 and 35 years, from the companies Gojek and Grab. The interview results revealed that the perceived barriers for online motorcycle taxi drivers were primarily related to order availability and weather conditions. Drivers' perceptions of PAK were influenced by various factors, and the application of occupational health principles was seen as essential in mitigating the risk of PAK. Similarly, drivers' perceptions of work accidents were influenced by several factors, with the application of safe driving principles being crucial to reducing the risk of such accidents. The rules and facilities provided by the companies sufficiently support the drivers in implementing K3 principles concerning work safety, whereas, in terms of health, the support was limited to facilitating health insurance registration and payment through the app. Conclusion: Online motorcycle taxi drivers face several barriers in their work. The application of health principles can mitigate the risk of PAK, and safe driving principles can reduce the risk of work accidents. Solutions to support online motorcycle taxi drivers in implementing K3 principles include 1) peer support, 2) provision of regular health check facilities, 3) work readiness checklists, and 4) K3 training.